Itinerant ferromagnetism in an atom trap - Berdnikov, I; Coleman, P; Simon, S (2009)
We propose an experiment to explore the magnetic phase transitions in interacting fermionic Hubbard systems and describe how to obtain the ferromagnetic phase diagram of itinerant-electron systems from these observations. In addition, signatures of ferromagnetic correlations in the observed ground states are found: for large trap radii (trap radius RT >4, in units of coherence length ξ), ground states are topological in nature-a "skyrmion" in two dimension, and a "hedgehog" in three dimension. © 2009 The American Physical Society.